The correlation between work posture and lower back pain among tailors - Putu Ayu Bintang Anjali; Sayu Aryantari Putri Thanaya; Agung Wiwiek Indrayani; Ni Komang Ayu Juni Antari (Universitas Udayana dan Diaspora Taipei Medical University, 2024)
Background: Tailoring is an occupation pursued by a significant portion of the Indonesian population, and it is closely associated with working in a seated position. Tailors often experience rigid work postures and static muscle loads, which, if left unaddressed for extended periods, can increase the risk of work-related illnesses, one of which is lower back pain. Methods: This study employed an analytical observational method with a cross-sectional approach. The research subjects were determined using a total sampling technique. The total number of research subjects involved in this study was 37, adjusted based on inclusion and exclusion criteria. The research data included the level of work posture risk which was measured by the Rapid Upper Limb Assessment (RULA) and lower back pain measured by the Numeric Pain Rating Scale (NPRS). Results: The Spearman's rho hypothesis test was used to analyze the relationship between work posture and the occurrence of lower back pain at the garment in Bali, yielding a result of p = 0.000 (p < 0.05), indicating a significant correlation. Conclusions: This research concluded that a significant correlation between work posture and lower back pain among tailors in Bali.